Assessment of landslides in the Banjarsari area, Ciamis Regency, Indonesia: A morphographic and morphometric approach - Ibrahim, Mochammad Malik; Alfalah, Jasmin Arya; Zahra, Salsabila Az (Journal of Degraded and Mining Lands Management, 2026)
Landslides are among the most common geological hazards in Indonesia, particularly in areas with steep topography and complex geology. This study was conducted in the Banjarsari Area, Ciamis Regency, West Java Province, Indonesia, to assess landslide susceptibility using morphographic and morphometric approaches based on Digital Elevation Model (DEM) data and field observations. The results showed that more than 35% of the study area has slope gradients exceeding 15%, indicating it is landslide-prone terrain. Hilly morphographic conditions and morphometric characteristics influenced by geological structural control contribute to the occurrence of translational, rotational, and rockfall-type landslides identified during field surveys. Landslide susceptibility was further quantified using the Landslide Susceptibility Index (LSI), which integrates slope gradient, landform, drainage pattern, slope aspect, and field indicators. The spatial distribution of LSI values ranges from low to very high susceptibility and shows strong agreement with observed landslide locations. Areas with higher LSI values indicate zones of greater slope instability and provide an objective basis for prioritizing landslide mitigation efforts and for supporting risk-informed land-use planning in the study area.